2021
DOI: 10.1080/0886022x.2021.1918558
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in patients undergoing peritoneal dialysis: a systematic review and meta-analysis

Abstract: Aim: Inconsistent investigations of the risk factors for all-cause mortality in patients undergoing peritoneal dialysis (PD) were reported. The present meta-analysis aimed to assess the impact of some clinical characteristics on the risk of mortality in PD patients. Methods: PubMed and Embase were systematically searched for studies evaluating the risk factors for all-cause mortality in PD patients. Hazard ratio (HR) and 95% confidence interval (CI) were derived using a random-effect or fixed-effect model cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
2
25
0
1
Order By: Relevance
“…Furthermore, it was found that 51% of the patients who died had DM, in whom, overall mortality and the incidence of major cardiovascular events were significantly higher than in the non-diabetic population, a finding that is probably related to the higher frequency of traditional risk factors for cardiovascular disease and the association with a greater degree of overhydration at the start of therapy in this population. These findings are related to those reported in a meta-analysis that analyzes the risk factors for all-cause mortality in patients on PD, where age, CVD, and DM are associated with a higher risk of cardiovascular mortality and all-cause mortality, as well as a higher rate of hospitalizations for cardiovascular causes with AMI and CVD predominating (4).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, it was found that 51% of the patients who died had DM, in whom, overall mortality and the incidence of major cardiovascular events were significantly higher than in the non-diabetic population, a finding that is probably related to the higher frequency of traditional risk factors for cardiovascular disease and the association with a greater degree of overhydration at the start of therapy in this population. These findings are related to those reported in a meta-analysis that analyzes the risk factors for all-cause mortality in patients on PD, where age, CVD, and DM are associated with a higher risk of cardiovascular mortality and all-cause mortality, as well as a higher rate of hospitalizations for cardiovascular causes with AMI and CVD predominating (4).…”
Section: Discussionsupporting
confidence: 73%
“…End-stage renal disease (ESRD), as well as other chronic diseases, generate systemic effects at the cardiovascular, pulmonary, endocrine, neurological, and muscular levels, among others, which lead to complications and a decrease in longterm survival (2). Muscular affectation due to the presence of sarcopenia or dinapenia is frequent in patients who join dialysis programs (3,4). The impact of cardiometabolic risk factors and other chronic diseases prevalent in this population are also added (5).…”
Section: Introductionmentioning
confidence: 99%
“…The causes of mortality in PD are both numerous and complex. Indeed, age, CV disease, DM, PD peritonitis episodes, higher body mass index, higher alkaline phosphatase, inflammation, and anemia are all associated with PD mortality ( 32 ). The small effect size of PD duration and PD glucose load on mortality may be one of the reasons that the result was not significant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher HbA1c and non-diabetes patients were less associated with LVMI and LAD enlargement in our study. DM appeared to predict the risk of fatal cardiovascular events and all-cause mortality in PD patients [ 39 ]. But some dialysis patients tend to have false low HbA1c levels due to anemia and erythropoiesis-stimulating agents (ESAs) use.…”
Section: Discussionmentioning
confidence: 99%